Siltuximab for chimeric antigen receptor T-cell therapy–related CRS and ICANS: a multicenter retrospective analysis - Amneet Bajwa; Qiuhong Zhao; Marcus Geer; Chenyu Lin; James Westholder; Joseph Maakaron; Monalisa Ghosh; David Frame; Ahmed Galal; Justin Tossey; Nausheen Ahmed; Evandro Bezerra; et al. (Blood Advances)
Abstract: Chimeric antigen receptor T-cell (CAR-T) therapies are effective in many hematologic malignancies; however, adverse events including cytokine release syndrome (CRS) and immune effector cell–associated neurotoxicity syndrome (ICANS) can affect a significant number of patients. Those who develop refractory CRS or ICANS have few treatment options. Siltuximab, a monoclonal antibody binding circulating interleukin-6, has been proposed to have clinical activity in both CRS and ICANS. We conducted a multicenter retrospective analysis of siltuximab treatment for CRS and ICANS after CAR-T therapy in a real-world cohort from 6 academic centers. Fifty-four patients were evaluated. Sixteen patients had CRS previously treated with tocilizumab and 17 patients had ICANS previously treated with steroids. Of the patients with CRS at the time of siltuximab, 75% had improvement in CRS grade. Of the patients with ICANS at the time of siltuximab, 60% had improvement in ICANS grade. To our knowledge, this is the largest cohort of patients treated with siltuximab for CRS and/or ICANS after CAR-T therapies. Siltuximab appeared to be effective for both CRS and ICANS, including previously treated toxicities. These data support the use of siltuximab in CRS and ICANS as well as provide rationale for future prospective studies.